The Real Status of Online Training in the UAE from the Perspective of Teachers - Alrmamnh, Yahya Mohamed; Al-Draiseh, Abdullah Saleh; Saadi, Sultan Ali Al (Journal of Educational and Psychological Sciences, 2021)
This study aimed to find out the real status of online training in the United Arab Emirates from teachers' perspectives. The researchers used the descriptive analytical methodology to answer the questions of the study. For this purpose, they prepared a questionnaire consisting of (24) items divided into three dimensions. The sample of the study consisted of (228) teachers who were selected randomly. The study revealed that the teachers' estimates were highly (Strongly Agree) satisfied with the status of online training and each of the three dimensions (Trainers, Content of the training programs, and the training environment). The study also revealed the following:-There are no statistically significant differences at (a= 0.05) in the degree of teachers' estimation due to the (gender variable, academic qualification variable, variable of years of service).Based on what was achieved in this study, there is effectiveness in the online training provided to teachers in the United Arab Emirates in all three aspects: the trainers, the content of the training programs, the training environment. The study recommended the need to continue conducting online training and maintaining the improvement and generalization of all the conditions for its success in various emirates. It also recommended the need to investigate the real status of online training from the point of view of school principals and students.
Keywords: distance training; in-service training programs